Dried fruit intake causally protects against low back pain: A Mendelian randomization study - Huang, Jian; Xie, Zheng-Fu (Frontiers in Nutrition, 2023)
Background: Low back pain is the leading cause of years lived with disability worldwide. The aim of this study was to evaluate whether dried fruit intake causally protects against low back pain using two-sample Mendelian randomization (MR). Methods: We obtained summary-level data for dried fruit intake (N=421764) from the IEU Open GWAS Project. Forty-one independent genetic variants proxied dried fruit intake. The corresponding data for low back pain were derived from the FinnGen project (13178 cases and 164682 controls; discovery data) and the Neale lab (5423 cases and 355771 controls; replication data). We conducted univariable and multivariable MR analyses. Results: In the univariable MR analysis, the inverse variance weighted estimate showed that greater dried fruit intake was associated with decreased risk of low back pain (odds ratio (OR)=0.435, 95% confidence interval (CI): 0.287-0.659, P=8.657×10-5). Sensitivity analyses using the MR-Egger (OR=0.078, 95% CI: 0.013-0.479, P=0.009), maximum likelihood (OR=0.433, 95% CI: 0.295-0.635, P=1.801×10-5), weighted median (OR=0.561, 95% CI: 0.325-0.967, P=0.038) and Mendelian Randomisation Pleiotropy RESidual Sum and Outlier (MR-PRESSO) (OR=0.454, 95% CI: 0.302-0.683, P=4.535×10-4) methods showed consistent results. No evidence of directional pleiotropy was identified according to the Egger intercept (intercept P-value=0.065) or applying the MR-PRESSO method (global test P-value=0.164). The replication analysis yielded similar results. The multivariable MR revealed that the inverse association between dried fruit intake and low back pain was consistent after adjustment for fresh fruit intake, body mass index, current tobacco smoking, alcohol intake frequency, total body bone mineral density, serum 25-hydroxyvitamin D levels, and vigorous physical activity. Conclusion: This MR study provides evidence to support that dried fruit intake causally protects against low back pain.